A Concealment Aware UEP scheme for H.264 using RS Codes - Deevya Indoonundon; Tulsi Pawan Fowdur; Sunjiv Soyjaudah (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
H.264/AVC is currently the most widely adopted video coding standard due to its high compression capability and flexibility. However, compressed videos are highly vulnerable to channel errors which may result in severe quality degradation of a video. This paper presents a concealment aware Unequal Error Protection (UEP) scheme for H.264 video compression using Reed Solomon (RS) codes. The proposed UEP technique assigns a code rate to each Macroblock (MB) based on the type of concealment and a Concealment Dependent Index (CDI). Two interleaving techniques, namely Frame Level Interleaving (FLI) and Group Level Interleaving (GLI) have also been employed. Finally, prioritised concealment is applied in cases where error correction is beyond the capability of the RS decoder. Simulation results have demonstrated that the proposed framework provides an average gain of 2.96 dB over a scheme that used Equal Error Protection (EEP).